Effect Of Web-Based Learning To Increase Knowledge Of Basic Life Support For Nursing Students During The COVID-19 Pandemic - Addi Mardi Harnanto; Sunarto Sunarto ((JKG) Jurnal Keperawatan Global, 2022)
Background: COVID-19 does not discriminate based on geography, ethnicity, disability status, age, or gender. COVID-19 can be stopped from entering schools and spreading among infected students and employees, while also limiting disruption and safeguarding students and staff from discrimination. Basic life support is one of the critical skills that have to be mastered via way of means of nursing college students earlier than sporting out clinical placement in hospitals Due to the constraints of the COVID-19 Pandemic, a web-based learning media was developed to make it easier for students to learn about basic life support from wherever they are. Methods: This study is a comparative experimental study with a pretest-posttest design with a control group. Purposive sampling was utilized in this study.76 respondents participated in this study and were divided into two groups using the lottery method. The research instrument is form of questions about basic life support developed by the research team. Respondents were divided into 2 groups, namely the experimental group and the control group. The eperimental group was given action in the form of independent learning opportunities that were guided using the website while the control group was given treatment in the form of classical learning. Analysis techniques using t-tests. Results: There was an increase in scores between the pretest and the posttest in both groups. The value of the experiment group increased more than that of the control group. The treatment group's score increased by 3.5 points, while the control group's score increased by 1.9 points. The Sig result was 0.00 based on the t-test analysis. Conclusion: Web-Based learning increases nursing students' knowledge of basic life support during the COVID-19 Pandemic.